Emotional stimuli and motor conversion disorder - Voon, Valerie (Oxford University Press, 2010)
Conversion disorder is characterized by neurological signs and symptoms related to an underlying psychological issue. Amygdala activity to affective stimuli is well characterized in healthy volunteers with greater amygdala activity to both negative and positive stimuli relative to neutral stimuli, and greater activity to negative relative to positive stimuli. We investigated the relationship between conversion disorder and affect by assessing amygdala activity to affective stimuli. We conducted a functional magnetic resonance imaging study using a block design incidental affective task with fearful, happy and neutral face stimuli and compared valence contrasts between 16 patients with conversion disorder and 16 age- and gender-matched healthy volunteers. The patients with conversion disorder had positive movements such as tremor, dystonia or gait abnormalities. We also assessed functional connectivity between the amygdala and regions associated with motor preparation. A group by affect valence interaction was observed. Post hoc analyses revealed that whereas healthy volunteers had greater right amygdala activity to fearful versus neutral compared with happy versus neutral as expected, there were no valence differences in patients with conversion disorder. There were no group differences observed. The time course analysis also revealed greater right amygdala activity in patients with conversion disorder for happy stimuli (t = 2.96, P = 0.006) (with a trend for fearful stimuli, t = 1.81, P = 0.08) compared with healthy volunteers, with a pattern suggestive of impaired amygdala habituation even when controlling for depressive and anxiety symptoms. Using psychophysiological interaction analysis, patients with conversion disorder had greater functional connectivity between the right amygdala and the right supplementary motor area during both fearful versus neutral, and happy versus neutral ‘stimuli’ compared with healthy volunteers. These results were confirmed with Granger Causality Modelling analysis indicating a directional influence from the right amygdala to the right supplementary motor area to happy stimuli (P < 0.05) with a similar trend observed to fearful stimuli (P = 0.07). Our data provide a potential neural mechanism that may explain why psychological or physiological stressors can trigger or exacerbate conversion disorder symptoms in some patients. Greater functional connectivity of limbic regions influencing motor preparatory regions during states of arousal may underlie the pathophysiology of motor conversion symptoms.